Timing of Delivery in Women with Cardiac Disease - Rouse, Caroline E.; Easter, Sarah Rae; Duarte, Valeria E.; Drakely, Sheila; Wu, Fred M.; Valente, Anne Marie; Economy, Katherine E. (American Journal of Perinatology, 2020)
Objective Guidelines do not exist to determine timing of delivery for women with cardiovascular disease (CVD) in pregnancy. The neonatal benefit of a term delivery as compared with an early term delivery is well described. We sought to examine maternal outcomes in women with CVD who delivered in the early term period (370/7 through 386/7 weeks) compared with those who delivered later.Study Design This is a prospective cohort study examining cardiac and obstetric outcomes in women with CVD delivering between September 2011 and December 2016. The associations between gestational age at delivery and maternal, fetal, and obstetric characteristics were evaluated.Results Two-hundred twenty-five women with CVD were included, 83 (37%) delivered in the early term period and 142 (63%) delivered at term. While the early term group had significantly higher rates of any hypertension during pregnancy (18.1 vs. 7%, p = 0.01) and intrauterine growth restriction (22.9 vs. 2.8%, p < 0.001), there was no difference in high-risk cardiac or obstetric characteristics. No difference in composite cardiac morbidity was found (4.8 vs. 3.5%, p = 0.24). Women in the early term group were more likely to undergo cesarean delivery than women in the term group (43.4 vs. 24.7%, p = 0.004).Conclusion There is no maternal benefit of an early term delivery in otherwise healthy women with CVD. Given the known fetal consequences of early term delivery, this study offers support to existing literature suggesting term delivery in these women.Key Points
Keywords: cardiac disease in pregnancy; early term delivery; timing of delivery; congenital heart disease